Clinical significance of contrast extravasation on computed tomography immediately after thermal ablation for hepatic tumors - Dong Kyu Kim; Joon Ho Kwon; Kichang Han; Juil Park; Gyoung Min Kim; Man-Deuk Kim; Jong Yun Won (BMC Gastroenterology)
Abstract Background To evaluate the clinical significance of contrast extravasation observed on post-ablation computed tomography (CT) performed immediately following thermal ablation of hepatic tumors. Methods Between October 2014 and December 2023, 1,274 patients with 1,745 primary or metastatic hepatic tumors underwent ablation, including radiofrequency ablation, microwave ablation, and cryoablation. Among them, 30 patients (median age: 66 years) with contrast extravasation observed on post-ablation CT scans were retrospectively analyzed. The pre- and post-ablation hemoglobin and hematocrit levels were measured. Local tumor progression-free survival (LTPFS) and overall survival (OS) rates were evaluated. Results Among the 30 patients, angiography was performed in 6 patients. Contrast extravasation was observed on angiography in only two patients; contrast extravasation from the right inferior phrenic artery and intercostal artery was noted, and successful transarterial embolization was achieved. Conservative management was considered adequate without additional treatment in 28 of 30 patients. No significant differences were observed between the 1 day before and after ablation hemoglobin (12.9 g/dL; 12.0–13.8 g/dL vs. 12.5 g/dL; 11.5–13.8 g/dL, P = 0.102) and hematocrit (38.3%; 36.0–40.1% vs. 37.0%; 34.8–39.2%, P = 0.100) levels. During a mean follow up period of 23.3 ± 17.8 months, the LTPFS rates were 96.4% and 84.3% at 1 and 2 years, respectively. The OS rate after the procedure was 96.7%. Conclusion The presence of contrast extravasation on post-ablation CT was not clinically significant, when extravasation confined to intrahepatic or venous origins. However, transarterial embolization is required if contrast extravasation is detected in the extrahepatic arteries.